The collaboration between early childhood intervention and child protection systems: the perspectives of professionals - Albuquerque, J.; Aguiar, C.; Magalhães, E. (Children and Youth Services Review, 2020)
This qualitative study, conducted in Portugal, aimed to understand professionals' perspectives on the collaborative processes between the Early Childhood Intervention (ECI) and the Child Protection Systems. Participants in this study were 19 professionals from 7 Local Intervention Teams of the ECI system, including 8 professionals with coordinating roles. We conducted content analysis following semi-structured interviews. Participants described collaboration as the cooperation between professionals and services, aiming to improve intervention with children and families. Professionals argued that the main advantage of a collaborative relationship was the promotion of effective interventions. However, collaborative practices were mainly described as limited due to communication problems (e.g., insufficient, untimely). Finally, professionals suggested that limited time and resources were the greatest barriers to collaboration while close contacts and relationships among professionals were viewed as the main facilitators. Implications for practice and policy towards enhancing collaboration processes are discussed.